Triphalangeal thumb: case report and literature review - Pedrazzini, Alessio; Pogliacomi, Francesco; Colacicco, Alessandra; Galavotti, Cristina; De Filippo, Massimo; Tocco, Silvio; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2015)
Triphalangeal thumb (TPT) is a relatively rare congenital anomaly of the hand with evidence for autosomal dominant transmission. Surgical treatment is not always required, but according to Wood’s classification it is related to the shape of the extra phalange. In this article, we present a case of  a 32 year old woman with isolated bilateral TPT.